Effectiveness of Activated Carbon Filter Corn Cob and Durian Skin Dnature Lowers Lead Levels (Pb) in Rain Water - Budiman; Nur Rismawati; Alwin (Universitas Muhammadiyah Palu, 2022)
Lead levels (Pb) cause adverse effects on health, toxic effects on the gastrointestinal tract, nerves and kidneys. This study aims to determine the effectiveness of using activated carbon filters for corn cobs and durian husks in reducing lead (Pb) levels in rainwater that passes over zinc. This type of study is an experiment by comparing the decrease in lead (Pb) levels before and after the filtration of activated carbon of corn cobs and durian husks with adsorption times of 30 minutes and 35 minutes. The results of the study before processing obtained lead (Pb) levels in 3 different locations, namely 0.079 mg / l, 0.053 mg / l, and 0.059 mg / l. After processing the activated carbon of corn cobs and activated carbon of durian skin, it is effective in reducing lead (Pb) levels < 0.05 mg / l in accordance with water quality standards according to Permenkes No. 23 of 2017. This can be seen after filtration of activated carbon of corn cobs with an adsorption time of 30 minutes, which is 91% of 0.007 mg / l in PM houses, and an adsorption time of 35 minutes, which is 100% of 0.0 mg / l in HD houses. Then after filtration of activated carbon durian skin with an adsorption time of 30 minutes, which is 64.4% of 0.021 mg / l in HD houses, and an adsorption time of 35 minutes, which is 60.4% of 0.021 mg / l in SU houses. This research suggests that health agencies provide empowerment to the community about the management of clean water and the use of activated carbon in reducing levels of harmful metals, especially lead (Pb).